Council for World Mission: A Case Study and Critical Appraisal of the Journey of Partnership in Mission - van der Water, Desmond (International review of mission, 2008)
When the Council for World Mission was founded in 1977, the organization held up partnership in mission as the key constituting factor of its identity as a new mission organization. This paper critically appraises the organization's missional journey over three decades, with particular reference to its vocation as a partnership in mission.